Birth weight and risk of paediatric Hodgkin lymphoma: Findings from a population-based record linkage study in California. (December 2016) - Triebwasser, Corey; Wang, Rong; DeWan, Andrew T.; Metayer, Catherine; Morimoto, Libby; Wiemels, Joseph L.; Kadan-Lottick, Nina; Ma, Xiaomei
Abstract: Objective: To evaluate the relationship between birth weight (along with a variety of pre and perinatal characteristics) and the risk of paediatric Hodgkin lymphoma (HL) diagnosed at age <20 years. Method: We linked California statewide birth records from 1978–2009 and cancer diagnosis data from 1988–2011 to conduct a population-based case–control study with 1216 cases and 4485 controls (matched on birth month and year, sex, and race/ethnicity). Conditional logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (95% CI) of paediatric HL overall and by age of diagnosis, controlling for other perinatal factors. Results: Compared to children with a normal birth weight (2500–3999 g), those who had a high birth weight (≥4000 g) had an increased risk of paediatric HL overall (OR = 1.23, 95% CI: 1.02–1.48) after adjusting for birth order, maternal age at the time of delivery, and paternal age at the time of delivery. The magnitude of association appeared larger for subgroups of children whose age of diagnosis was 0–10 years (OR = 1.56, 95% CI: 1.04–2.24) or 15–19 years (OR = 1.43, 95% CI: 1.11–1.83), while no association was observed in 11–14 year olds. Compared with firstborn children, those who were third or higher in birth order had a reduced risk of paediatric HL overall (OR = 0.80, 95% CI: 0.67–0.95), and this association also varied by age of diagnosis. Conclusions: In this study with the largest number of paediatric HL cases, high birth weight was associated with an increased disease risk for most but not all ages of diagnosis. The different findings by age of diagnosis regarding both birth weight and birth order underscore the importance to stratify paediatric HL by age at diagnosis in future etiological investigations. Highlights: In this study, we found paediatric Hodgkin lymphomas diagnosed at different ages might have distinct etiological profiles.